MONOLITH IN A HOLLOW: PALEOFUTURISM AND EARTH ART IN STANLEY KUBRICK’S 2001: A SPACE ODYSSEY - Wamberg, Jacob (The Nordic Journal of Aesthetics, 2020)
This article analyses 2001 in terms of what I term paleofuturism. Fusing deep future and deep past, this cyclical figure reconciles rational machinic intelligence with diverse repressed temporal layers: archaic cultures, the embryonic state of individuals, and bygone biological and geological eras. In 2001, paleofuturism is nourished by Nietzsche’s Übermensch of the future, reborn as a child, and by Jungian ideas of individuation, the reconciliation with the shadow of the collective unconscious that leads to the black cosmos itself. Further paleofuturist contexts for 2001 are explored in the so-called “ancient astronaut thesis” of science fiction, speculative science, and pseudo-science. Finally, in minimalism and earth art of the late 1960s we meet a structural parallel to 2001’s bypassing of the organic human body, one that bridges the inorganic entropic realities of deep future and deep past.